A giant abdominal hematoma caused by seatbelt injury led to the development of shock. Issue 8 (20th June 2015) - Nishino, Tomoya; Morita, Seiji; Sakurai, Keiji; Watanabe, Yasue
Key Clinical Message: Trauma to soft tissues is an important consideration in cases of seatbelt injury, as soft‐tissue injury can cause shock. Careful observation for hours in the clinic at least, along with appropriate imaging studies, is necessary if signs of a seatbelt injury exist. Abstract : Trauma to soft tissues is an important consideration in cases of seatbelt injury, as soft‐tissue injury can cause shock. Careful observation for hours in the clinic at least, along with appropriate imaging studies, is necessary if signs of a seatbelt injury exist.